(untitled) (Polis (Santiago), 2018)
The paper addresses the problem of subjectivity and everyday experience of female migrant who work as domestic caregivers into two highly feminised migration flows with high concentration of immigrant women in domestic service (Spain and Chile). A comparative approach will be taken to examine South-north and South-south migration flows regards on the expectations and motivations that shape female migration patterns, the meaning of care work in the employment of migrant women in the receiving countries, as well as appraisal and meaning that care work has for its protagonists, both from emotional perspective and the ‘public good’ framework. The results presented here are based on a broader research project whose primary information was obtained from the application of 67 in-depth interviews with different actors involved in the social relation of care.